DEVELOPMENT OF WEB-BASED CHEMICAL LEARNING MEDIA IN COLOID SYSTEM TOPIC USING WORDPRESS - Oktaviani, Elmaya; Cahyana, Ucu; Purwanto, Agung (JTK (Jurnal Tadris Kimiya), 2020)
The study aimed to develop web-based learning media on colloidal system topic using wordpress CMS. It comes from challenges to make an attractiveÂ learning system for students. The research method ADDIE model developed by Dick and Carrey. The research instrument was questionaires. This learning media had been validated by media experts, material experts, chemistry educators and field trials. The result showed that the learning media is valid and feasible to be used in teaching and learning activities on system colloid lessons. It is proven based on the average score which is converted in to good and very good categories according to the ideal assessment criteria. While the result of small group trial showed the average scores of 19 and 19.4 for aspects of learning material and 35.5 and 38.1 for aspects of appearance and operation are both categorized as a good category.